2011
DOI: 10.1016/j.jala.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Preparative Supercritical Fluid Chromatography System for Compound Library Purification: The TharSFC SFC-MS Prep-100 System

Abstract: Preparative HPLC-MS is often the method of choice for purification of small amounts (<100 mg) of diverse new molecules, such as compound libraries for drug discovery. The method is robust, well proven, and widely applicable. In contrast, preparative supercritical fluid chromatography coupled with mass spectrometry (SFC-MS) has seen only slow acceptance for the same application—despite some potential scientific and economic advantages. One of the reasons for slow adoption of SFC-MS is the lack of well-proven, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…▶ Table 3 Percentage of polar styrax compounds (1)(2)(3)(4)(5)(6) The developed workflow is easily adaptable and has already been successfully applied in our lab to vanilla pods and star anise for the extraction and analysis of 3 and 6 (data not shown). Especially, in respect to the need for highly pure reference standards for quality control of herbal drugs or the demand for food-grade extraction, SFx workflows offer many new possibilities which will definitely be in the focus of future natural product research.…”
Section: Resultsmentioning
confidence: 99%
“…▶ Table 3 Percentage of polar styrax compounds (1)(2)(3)(4)(5)(6) The developed workflow is easily adaptable and has already been successfully applied in our lab to vanilla pods and star anise for the extraction and analysis of 3 and 6 (data not shown). Especially, in respect to the need for highly pure reference standards for quality control of herbal drugs or the demand for food-grade extraction, SFx workflows offer many new possibilities which will definitely be in the focus of future natural product research.…”
Section: Resultsmentioning
confidence: 99%
“…Our adoption of SFC−MS over the past two years for purification of chiral compounds and diverse achiral small molecule libraries has demonstrated that the technology is a valuable asset for drug discovery. The Waters SFC−MS Prep‐100 is a significant advancement over previous generation of SFC instrumentation in terms of performance, synchronization, and overall robustness . However, the lack of a commercially available instrument capable of providing both RPLC and SFC capabilities with mass‐driven fractionation resulted in the development of this dual‐mode system.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the relatively low toxicity, high diffusivity, low viscosity and high solvating power of the mobile phase used (supercritical CO 2 , SCCO 2 ), SFC is regarded as a greener separation tool complementing or replacing gas chromatography (gC) and high-performance liquid chromatography (HPlC) [5]. With so many merits, SFC has attracted wide interests in the pharmaceutical industry as a useful separation technique for high-throughput analysis [6,7], purity assessment [8], structure characterization [9] and purification for pharmaceutical compounds [10,11]. In addition, SFC can also be used to perform high-precision biomolecular analysis [12], especially for hydrophobic metabolites, because of the low polarity of the mobile phase used.…”
Section: Introductionmentioning
confidence: 99%